Epidemiological Study and Estimating of Accidents Distribution in Construction Industry Workers in Yazd City by Appling Time Series until 2011. - Halvani, Gholamhossein; Ibrahemzadih, Mehrzad (International Journal of Occupational Safety and Health, 2012)
Millions of construction industry accidents occur in the world cause troubles and injuries to workers and consequently economical loosing every year. The aim of this paper is an epidemiological study and determination of an estimator model for accidents of construction industry until 2011, for the first time, in Yazd city. This study is a descriptive, analytical and modeling. The questionnaire contains the variables such as age, occupation, type of accident, injured part and the results of accident. Fatal rate of workers who hadn’t insurance was more than those who had which was statistically significant (p < 0.001). The most rate of accident was falling (48.58%) and the less was chocking (29%). The highest level of injured was related to hands and feet and then head injury (22.27%). The relationships of accident results with kind of occupation and also part of body were statistically significant in construction industry (p<0.001). After testing many models, time series model of quadratic form was the closest model to the trend of data. This model estimation shows that if the situation be the same as now in 1390 the cases will be more than 300 per year. So this model recommended making change in the trend for preventing the accidents in future. DOI: http://dx.doi.org/10.3126/ijosh.v2i1.5917 International Journal of Occupational Safety and Health, Vol. 2 No. 1 (2012) 26-30